Respuesta :
x3 - 10x2 + 24x
= x(x2 - 10x + 24)
= x(x2 - 4x - 6x + 24)
= x[ x(x - 4) - 6(x - 4) ]
= x(x - 6)(x - 4)
= x(x2 - 10x + 24)
= x(x2 - 4x - 6x + 24)
= x[ x(x - 4) - 6(x - 4) ]
= x(x - 6)(x - 4)
The factorization of the given trinomial is x(x² - 10x +24).
What is factorization of a polynomial?
"The factorization of polynomials expresses a polynomial with coefficients in a given field or in the integers as the product of irreducible factors with coefficients in the same domain."
Given trinomial is:
x³ - 10x² + 24x
= x(x² - 10x +24)
Therefore by factorizing the given trinomial, we get: x3 - 10x2 + 24x.
Learn more about factorization of a polynomial here: https://brainly.com/question/10744988
#SPJ2